Identification of ColE1 DNA sequences that direct single strand-to-double strand conversion by a phi X174 type mechanism. - Nomura, N (1982)
A DNA single-strand initiation sequence, named rriA (called rri-1 previously), was detected in the origin region (Hae II fragment E) of the ColE1 plasmid [Nomura, N. & Ray, D. S. (1980) Proc. Natl. Acad. Sci. USA 77, 6566-6570]. Another site, called rriB, has been found on the opposite strand of Hae II fragment C. Both rriA and rriB (i) direct conversion of chimeric M13 phage single-stranded DNA to parental replicative form DNA in vivo by a rifampicin-resistant mechanism that is dependent on the dnaG and dnaB gene products, (ii) provide effector sites of dATP hydrolysis by primosomal protein n', and (iii) require the same primosomal proteins as phi X174 DNA for directing the in vitro conversion that rriA is the DNA sequence that determines the mechanism of lagging strand synthesis of ColE1 DNA and that the mechanism of discontinuous synthesis involves the primosomal proteins utilized in the in vitro conversion of phi X174 single strands to the double-stranded replicative form.